Employment shifts in Europe from 1997 to 2021: From job upgrading to polarisation - Sergio Torrejón Pérez; John Hurley; Enrique Fernández-Macías; Elisa Staffa (European Commission, Joint Research Centre (JRC), 2023)
This article analyses shifts in employment structures in a selection of eight EU countries (the Czech Republic, Germany, Spain, France, Ireland, Italy, Romania and Sweden), as well as employment dynamics at the aggregate EU level. This is done for four periods, separated by the financial crisis and the outbreak of the COVID-19 crisis: 1997-2007, 2008-2010, 2011-2019 and 2019Q4-2021Q4. Results show that there is a wide diversity of patterns of structural change across periods and countries in Europe. During the expansive phase of the business cycle (1997-2007), the pattern that was more widespread was job upgrading, with the number of workers increasing more in mid-high and high-paid jobs (especially in private and public services). Some important deviations are identified, i.e., the case of Germany and France experiencing job polarisation, and Romania being the only country of our sample that experienced net employment losses from 1997 to 2007. During the financial crisis (2008-2010) and the following period (2011-2019), the patterns of structural change were much more diverse. Workers that were hardest hit by the financial crisis were more likely to be located in the middle of the wage structure, generating in some cases (such as in Ireland, Spain and France, apart from the EU8) job polarization. The global financial crisis impacted hardest on male workers and workers that were employed in construction and manufacturing, while the number of workers in public services continued increasing. From 2011 to 2019, net employment growth was mainly driven by the increase in the size of service jobs, with employment in private services growing in a polarised way and public services promoting upgrading. In the EU8, as well as in Germany, Romania and Sweden we identify patterns of job upgrading or close variants (mid-upgrading), while in the Czech Republic, France, Italy, Ireland and Spain the shape of the pattern of employment change was more similar to one of job polarization. Finally, the COVID-19 crisis had an asymmetric impact, impacting mainly employment in low-paid in-person service activities and agriculture. Although women in low-paid jobs were initially more affected by men, it's also true that later the resilience of better paid jobs benefited more female workers than male workers.
Keywords: 330; job polarisation; economic restructuring; structural change; employment growth